Engineering aspects of food biotechnology - Teixeira, José António Couto, 1957-; Vicente, António (CRC Press, 2014)
"Preface Food biotechnology has had a very significant and growing impact on the food industry activity in recent years and such impact is clearly set to keep increasing. Food biotechnology's typical developments and applications have occurred in the fields of genetics and in enzyme- and cell-based biological processes, aiming at producing and improving food ingredients and foods themselves. While these developments and applications are usually well reported in terms of the underlying science, there is a clear lack of information on the engineering aspects of such biotechnologybased food processes. This book provides a comprehensive review on those aspects, from the development of food processes and products to the most important unit operations implied in food biotechnological processes, also including food quality control and waste management. The book is intended for food technologists and engineers working either as food developers, processors, or food process controllers. Undergraduate and postgraduate students and researchers will also find the materials covered in this book an invaluable contribution to their learning and work. This book is divided into three parts: engineering aspects of the use of biotechnology in the development of food processes and products, unit operations in food biotechnology, and waste management in the food industry"-- Resumé vydavatele
Keywords: potravinářská technologie; potravinářská biochemie; biotechnologie; food technology; food biochemistry; biotechnology; sborníky; papers of several authors